Kerukunan Beragama Warga Kristen dan Muslim di Komunitas Kristiani - Wardah, Amil Cholisna (Proceedings of Annual Conference for Muslim Scholars, 2019)
This article was written as a result of research on the relationship between Christianity and Islam in the Christian community. The research process was carried out qualitatively using a phenomenological approach and resulted in the conclusion that although Muslims in Peniwen Village, Kromengan Subdistrict, Malang Regency are minorities in the Christian Community, the interaction between Muslims and Christians in the village was very friendly, mutual cooperation and unpretentious even though different nuances are still very pronounced. Even Muslim citizens are given the freedom to implement the teachings of Islam in full. This is evident from the permission of the Mujahidin Foundation based in Malang to buy land to be built by a church from the Pentecostal sect above, even though Christians know that the land they sell will be used to establish a Muslim orphanage with the name "Dar ar-Rahman lil Aitam ". The Christian community also did not try to prevent the construction of the Ar-Rahman Mosque in Peniwen village. This phenomenon shows that the relationship between Christianity and Islam within the Christian community can produce harmonious harmony in life and social interaction that is full of tolerance